20,000 Leagues Under the Sea - Verne, Jules 1828-1905.; Vogel, Malvina G.; Pablo Marcos Studio (Edina, Minn. : ABDO Pub., 2002)
Fiction
Originally published: New York : Playmore : Waldman Pub., 1990.
Keywords: Submarines -- Fiction; Sea stories; Fiction